Perjanjian Waralaba Ditinjau Dari Aspek Hukum Keperdataan Dan Hukum Kekayaan Intelektual Serta Perlindungan Hukum Bagi Para Pihak Dalam Perjanjian Waralaba - ARDIANSYAH SAPUTRA; URBANISASI URBANISASI (Peneliti.net, 2023)
In line with the era of transformation and globalization that exists throughout the world, it will have an impact on aspects of the development of business concepts. Like d and as a new face in business development, the purpose of writing is to make readers understand the franchise agreement rather than the legal aspects of intellectual property. , analyzing and collecting data, the results of writing the Scope of Intellectual Property Rights (IPR). Special Rights: In the franchise agreement, the franchisee obtains special rights to use IPR from the company that grants the franchise.